Photometric Stereo Method Used for Woven Fabric Density Measurement Based on 3D Surface Structure - Endang Juliastuti; Irwan Setiawan; Vebi Nadhira; Deddy Kurniadi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The measurement of the density of woven fabrics based on the vision method has been widely developed. This study used a photometric stereo method to measure the warp and weft density of woven fabrics based on the 3D surface structure. Six 2D images of the fabric were recorded, each with a different lighting direction. The six images were then reconstructed using the unbiased photometric stereo algorithm to produce the three-dimensional surface structure. The reconstructed image was used to detect and correct the skew angle with the Hough transform. For each image, a depth profile was made toward the x-axis to get the weft curve and towards the y-axis to get the warped curve. The two depth curves were filtered using a locally weighted smoothing (LOESS) filter. This study successfully measured the density of woven fabric with an average error for warp and weft of 0.64% and 0.45%, respectively.